Procedural planning of CS‐based indirect mitral annuloplasty using CT‐angiography. Issue 7 (25th June 2021) - Rottländer, Dennis; Gödde, Miriel; Degen, Hubertus; Ögütcü, Alev; Saal, Martin; Haude, Michael
Abstract: Objectives: Coronary sinus (CS) based mitral annuloplasty using the Carillon device could be limited by compromise of the left circumflex artery (Cx). Background: Computed tomography (CT) might be a feasible tool for preprocedural planning of indirect mitral valve annuloplasty. Methods: In a retrospective analysis, 25 patients underwent Carillon device implantation and received CT‐angiography (CTA) analysis prior to CS based percutaneous mitral valve repair. We used a retrospective approach with preprocedural CTA and intraprocedural coronary sinus angiography (CSA) measurements to determine the CS to Cx distance at the occlusion or compression point or in the distal landing zone in absence of Cx compromise. Results: According to left coronary artery angiography, we identified 7 patients with Cx occlusion, 7 with Cx compression and 11 without Cx compromise. No difference in minimal CS to Cx distance between the three groups could be obtained. Also, neither distal CS diameter nor distal Carillon anchor size were related to Cx impingement. However, ROC analysis identified a CS to Cx distance of <8.6 mm specifically in the distal device landing zone to predict Cx compromise. Furthermore, CTA was accurate in assessing device length in comparison to CSA, but failed predicting Carillon device anchor size. Conclusions: CTA derived CS to Cx distance in the device landing zone might be helpful to predict Cx occlusion during Carillon device implantation. Furthermore, CTA predicted CS length but not anchor size correctly. Therefore, CT‐angiographic procedural planning might help improving the results of percutaneous CS‐based mitral valve repair.